Characterization and Genomic Analysis of the First Podophage Infecting Shewanella, Representing a Novel Viral Cluster - Dong, Yue; Zheng, Kaiyang; Zou, Xiao; Liang, Yantao; Liu, Yundan; Li, Xiang; Shao, Hongbing; Sung, Yeong Yik; Mok, Wen Jye; Wong, Li Lian; McMinn, Andrew; Wang, Min (Frontiers in Microbiology, 2022)
Shewanella is a common bacterial genus in marine sediments and deep seas, with a variety of metabolic abilities, suggesting its important roles in the marine biogeochemical cycles. Here, a novel lytic Shewanella phage, vB_SInP-X14, was isolated from the surface coastal waters of Qingdao, China. The vB_SInP-X14 contains a linear, double-strand 36396-bp with the G+C content of 44.1% and harbors 40 predicted ORFs. Morphological, growth and genomic analysis showed that it is the first isolated podovirus infecting Shewanella, with a short propagation time (40 minutes), which might be resulted from three lytic-related genes. Phylogenetic analysis suggested that vB_SInP-X14 could represent a novel viral genus, named Bocovirus, with four isolated but not classified phages. In addition, 14 uncultured viral genomes assembled from the marine metagenomes could provide additional support to establish this novel viral genus. This study reports the first podovirus infecting Shewanella, establishes a new interaction system for the study of virus-host interactions, and also provides new reference genomes for the marine viral metagenomic analysis.